Notes (1) On the Discovery of a Grave at Balneil, New Luce, Wigtownshire, containing a Partially Burnt Interment, a Cinerary Urn, a Bronze Chisel, a Bone Pin, and a Bead of Vitreous Paste. (2) On a Socketed Axe of Bronze found at Cambusmore, the Mound, Sutherlandshire. With Report on Bones from the Interment - Curle, Alexander; Bryce, Thomas (Proceedings of the Society of Antiquaries of Scotland, 1916)
The urn had been placed in an inverted position over a heap of human bones only partially incinerated. These represent two adult individuals. The chisel appears never to have been completed for use. Both the bead and pin had been burnt. The pin is an unusual type. The axe is unusual for its herring-bone ornamentation which has been incised on it around the socket.